Volcanic Aggregates for the Production of Asphalt Mix - Arce, Mario (2025)
The long-term performance of asphalt mixtures largely depends on the quality of the aggregates and the manner in which they are handled during the production and placement processes. In general terms, approximately 94% to 95% of the total weight of the mixture corresponds to the aggregate materials (when these exhibit absorption rates between 2.0% and 1.0%). The production process of asphalt concrete must be governed by a rigorous quality control system in order to maintain oversight at every stage of the production process. This is an essential requirement for achieving a high-quality product that consistently meets the specifications. In accordance with the aforementioned, the quality of the aggregate sources, as well as the methods of extraction and handling of these materials, as the predominant RAW MATERIAL, are direct determinants of the quality of the final product.